Connexin variations and deafness. (29th September 2015) - Rangan, S; Umapathy, D; Kennedy, V; Belk, R; Trump, D
Abstract : Connexins are the building blocks of gap junctions. Mutations in connexin are the most common cause of non-syndromic hereditary deafness. The authors looked at the results of connexin mutations in children identified with varying types (unilateral and bilateral) and degrees of their hearing losses since 2002 in Bolton. Our case mix consisted of children identified through the Newborn Hearing Screening Programme, which was introduced in our area in 2003, and older children with hearing loss already in the system. Connexin 26 was tested in all children identified with permanent childhood hearing impairment, but more recently connexin 30 is also being tested. The authors present the variability of mutations in connexin in relation to their phenotype.